2019
DOI: 10.1038/s41415-019-0488-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of the dental hospital-based paediatric liaison nurse in safeguarding children

Abstract: This is a repository copy of Role of the dental hospital-based paediatric liaison nurse in safeguarding children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The group of ten papers that spanned health and social care (Table 11) identified similar themes to the social care papers. Promising initiatives to promote awareness included some local authority partnership child sexual exploitation services (though other related services worked less well) 152 ; joint protocols between adult mental health and children's social services 153 ; and a paediatric dentistry liaison service 154 based in a hospital but working between community and social services. In contrast to these positive local examples, studies with more of a national focus often identified deficiencies in the availability of services and/or training 155,156 or variations in the delivery of a specific intervention 157 .…”
Section: Trainingmentioning
confidence: 99%
See 4 more Smart Citations
“…The group of ten papers that spanned health and social care (Table 11) identified similar themes to the social care papers. Promising initiatives to promote awareness included some local authority partnership child sexual exploitation services (though other related services worked less well) 152 ; joint protocols between adult mental health and children's social services 153 ; and a paediatric dentistry liaison service 154 based in a hospital but working between community and social services. In contrast to these positive local examples, studies with more of a national focus often identified deficiencies in the availability of services and/or training 155,156 or variations in the delivery of a specific intervention 157 .…”
Section: Trainingmentioning
confidence: 99%
“…Spencer et al were the only authors to include a comparison group, although their study only included routine data on a small number of patients 154 . Four included studies (Table 12) focused on initiatives involving use of routine data to improve awareness of safeguarding at the system level in health and/or social care [163][164][165][166] .…”
Section: Trainingmentioning
confidence: 99%
See 3 more Smart Citations